Penggunaan E-Modul Interaktif dalam Meningkatkan Kemampuan Literasi Siswa - Sape, Herwandi; Lukman; Sambara, Piether Magi (Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the effectiveness of using interactive e-modules in improving the literacy skills of Fisheries Department students at SMK Negeri 1 Maros. Using a qualitative approach, data was collected through observation, interviews and document analysis. The results showed that the interactive e-module was able to increase students' interest in reading, material comprehension, and analysis skills. Students are more motivated to learn because e-modules present material visually and interactively through text, images, videos, and simulations. In addition, teachers also feel a positive impact in learning, with increased active participation of students. This finding is in line with constructivism theory that emphasizes experiential learning and interaction. This study recommends the wider use of e-modules in vocational education to improve learning quality.